2018
DOI: 10.4103/ejd.ejd_180_17
|View full text |Cite
|
Sign up to set email alerts
|

Alexidine versus chlorhexidine for endodontic irrigation with sodium hypochlorite

Abstract: Objective:The objective of this study was to chemically evaluate precipitate formation on irrigation by different concentrations of chlorhexidine (CHX) and alexidine (ALX) with sodium hypochlorite (NaOCl).Materials and Methods:Six test tubes were prepared with 1 ml of 4% NaOCl. One milliliter of 2%, 1%, 0.5%, and 0.25% ALX was added to the first four, and in the last two, 1 ml of 2% CHX and 0.2% CHX was added, respectively. Samples were observed for color changes or precipitates at multiple time intervals. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
13
1
3
Order By: Relevance
“…Interaction between ALX and NaOCl has been described and discussed previously [19,24,25]. Kim et al [19] and Jain et al [24] suggested that ALX can be a potential alternative for CHX solution in endodontic treatment.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Interaction between ALX and NaOCl has been described and discussed previously [19,24,25]. Kim et al [19] and Jain et al [24] suggested that ALX can be a potential alternative for CHX solution in endodontic treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Interaction between ALX and NaOCl has been described and discussed previously [ 19 , 24 , 25 ]. Kim et al [ 19 ] and Jain et al [ 24 ] suggested that ALX can be a potential alternative for CHX solution in endodontic treatment. ALX was reported to have a similar chemical structure and properties and be even more potent in deactivating bacteria virulence factors than CHX.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations